Governance, Risk and Compliance (GRC) and Intellectual Capital's Impact on the Financial Performance of Indonesian Stock Exchange-Listed Companies That Win Top GRC Awards in 2020–2023 - Marpaung, Rika Hastuti Melianingsih; Fathonah, Andina Nur (Ekonomis: Journal of Economics and Business, 2025)
The purpose of this study is to ascertain and evaluate the impact of intellectual capital and governance, risk, and compliance (GRC) on the financial performance of 2019 BEI-listed businesses who get the Top GRC Awards. The approach used to determine the sample was purposeful sampling. During a four-year observation period, samples were obtained from eight companies, yielding thirty-two observations. Panel data regression and Eviews 12 are used in this study's data analysis. The findings of this study indicate that the financial performance (ROA) of the organization is significantly impacted by both intellectual capital and GRC (Governance, Risk, and Compliance). Financial performance (ROA) is not partially impacted by GRC. The financial success of the business is impacted by intellectual capital (ROA).